2019
DOI: 10.1177/1558944719846599
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Recurrent Multifocal Osteomyelitis of the Hand: A Rare Pediatric Condition

Abstract: Background: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare autoinflammatory condition characterized by bone pain and swelling, secondary to sterile bone osteolytic lesions. Estimated incidence is 1:1 000 000, with ~2% involving the hand. We present a case series of CRMO of the hand and review the available literature, with the aim of educating and raising awareness of this condition. Methods: A retrospective chart review was conducted for all patients presenting to the institution diagnosed with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Early reports suggest that the bisphosphonates offer promising efficacy in controlling CRMO, as well as safety of use [ 16 , 28 ], though results of recent studies indicated a burden of adverse events (AEs) in pamidronate therapy. In some patients, bisphosphonates were found to worsen bone pain [ 25 ], as well as lead to nausea, headache, fever and phlebitis [ 29 ], which ultimately decrease patients’ compliance [ 30 ]. The presented patient’s therapy was well tolerated and led to no significant AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports suggest that the bisphosphonates offer promising efficacy in controlling CRMO, as well as safety of use [ 16 , 28 ], though results of recent studies indicated a burden of adverse events (AEs) in pamidronate therapy. In some patients, bisphosphonates were found to worsen bone pain [ 25 ], as well as lead to nausea, headache, fever and phlebitis [ 29 ], which ultimately decrease patients’ compliance [ 30 ]. The presented patient’s therapy was well tolerated and led to no significant AEs.…”
Section: Discussionmentioning
confidence: 99%
“…As for therapeutic safety, its efficacy was also ambiguously discussed in recent studies. Some reports state that more than 2/3 patients treated with bisphosphonates achieved remission of CRMO symptoms and the progression of their disorder was inhibited, both in spinal and peripheral lesions [ 25 , 26 , 29 , 30 , 31 , 32 , 33 , 34 ]. It was also suggested that pamidronate leads to a rapid improvement in patient’s condition [ 26 ], which is in accordance with the observations of this study—within 1.5 years the reported patient returned to regular height range (50.-75. centile) from the threshold of 10. centile.…”
Section: Discussionmentioning
confidence: 99%